Mohammed Shawal Ian Fitri earns two degrees in Railway Engineering - Mimi Rabita, Abd Wahit (UMPSA, 2025)
BEIJING, 8 January 2024 – Mohammed Shawal Ian Fitri, 25, gained a unique and valuable learning experience as he graduated from two universities, completing a Dual Degree Programme in Railway Engineering at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) during his first and second years before continuing his studies at Beijing Jiaotong University (BJTU), China, sponsored by the Public Service Department (JPA) for his third and fourth years.